2014
DOI: 10.1111/jsm.12698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Different Testosterone Formulations in Female-to-Male Transsexual Persons

Abstract: Introduction Gender dysphoria is characterized by a strong discomfort with the gender assigned at birth and the urge to live as a member of the opposite gender. The acquisition of phenotypic features of the desired gender requires the use of cross-sex hormones. Female-to-male (FtM) transsexual persons are treated with testosterone to induce virilization. Aim The aim of the study was to assess the effects of three different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
130
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(153 citation statements)
references
References 40 publications
14
130
2
7
Order By: Relevance
“…Several studies note an increase in BMI for FtM patients after initiation of hormone therapy [9], [12], [13], [14]. Similarly, our study also saw an increase in BMI at Visit 1 in the FtM cohort, possibly due to increased muscle mass.…”
Section: 0 Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies note an increase in BMI for FtM patients after initiation of hormone therapy [9], [12], [13], [14]. Similarly, our study also saw an increase in BMI at Visit 1 in the FtM cohort, possibly due to increased muscle mass.…”
Section: 0 Discussionsupporting
confidence: 81%
“…Additionally, the FtM cohort showed an increase in creatinine at both Visit 1 and Visit 2; this would be an expected change if the FtM cohort had an average increase in muscle mass and thus muscle break-down products – a possibility given the observed increase in BMI. Testosterone use in hormone therapy for transgender men is associated with an increase in hemoglobin and hematocrit [11], [12], [13] [14], [15]. Our study also observed an increase in the hemogram parameters for the FtM cohort at Visit 1 and Visit 2.…”
Section: 0 Discussionsupporting
confidence: 60%
“…Similar studies of testosterone therapy in transgender men report decreases in HDL cholesterol, increases in triglycerides and either no change or increase in LDL cholesterol [30,31,33,34]. Cross-sectional studies, retrospective cohort studies, and a systematic literature review all have similar findings [21,26,32,35].…”
Section: Research To Datementioning
confidence: 71%
“…Small prospective studies exist which examine time to menstrual cessation with testosterone therapy [31,33]. Outcomes research on other transition related interventions, including speech therapy, are scattered throughout the literature [51,52,53].…”
Section: Research To Datementioning
confidence: 99%
“…The role of DXA is central in the study of body composition (BC) thanks to its ability to differentiate FM, non-bone lean mass (LM) and BMC at both the regional and the whole-body level ( Figure 2) (49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). DXA relies on the use of two X-ray beams of different energy; the measurement of the "R value" is calculated as the ratio between the degree of attenuation of the lower energy and the higher energy beam.…”
Section: Dxamentioning
confidence: 99%